Centrifugal Pumps as Extractors. Issue 5 (12th February 2020) - Schmitt, Philipp; Hlawitschka, Mark W.; Bart, Hans‐Jörg
Abstract: The generation of dispersions with defined droplet size distributions is important for liquid‐liquid extraction. In this respect, the capability of a centrifugal pump to generate dispersions was investigated for different operating points. For the analysis of the mixing process, a centrifugal pump was designed translucent. High‐speed images reveal the mechanism of particle breakup. Optical measurement technology and image processing with neural networks were used to determine droplet size distributions. The influence of flow rate, rotational frequency and holdup are discussed for a paraffin oil‐water system. Abstract : Centrifugal pumps can be used as mixing device in liquid extractors. Besides pumping, dispersions with defined droplet size distributions can be generated in liquid‐liquid two‐phase flows. According to a change of operating parameters the influence on drop size distributions is given.